Prediction of Oil Yield from Oil Palm Mesocarp Using Thermally Assisted Mechanical Dewatering (TAMD) - Hashim, H. (Springer Nature, 2020)
Thermally assisted mechanical dewatering (TAMD) is a new technology for the separation of solid/liquid. When applied to ânature-wetâ biomass, the TAMD process significantly enhances the separation yield. In the present study, TAMD was used to extract the crude palm oil (CPO) from mesocarp. The CPO yield of 70.77 wt was achieved at optimum parameters of 73.0Â Â°C, 6.7Â bar and 60Â min of extraction time. This CPO yield was comparable with previous works on the enzymatic extraction and hot compressed water extraction (HCWE) with CPO yield of 71.0 and 70.50 wt respectively. Apart from that, this value was higher for about 13.80 compared to commercial CPO extracted using screw press which obtained the oil yield of 61.0 wt. Based on the literatures, the highest CPO yield was obtained from supercritical CO2 extraction at 77.0 wt whereas the lowest CPO yield was extracted using subcritical R134a which gave 66.0 wt of oil yield. Nevertheless, the operational conditions of supercritical CO2 were 300Â bar and 80Â Â°C which were higher than that of TAMD. In conclusion, TAMD extraction has a potential to be an alternative method to extract CPO by producing higher oil yield. Â© 2020, Springer Nature Singapore Pte Ltd.